434 Reduced Postoperative Narcotics Consumption With Intraoperative Thoracolumbar Interfascial Plane (TLIP) Block Compared to Traditional Field Block. (1st April 2022) - Brusko, Gregory D.; Lu, Victor M.; Borowsky, Peter; Levi, David; Wang, Michael Y.
Abstract : INTRODUCTION: Given the increasing burden of narcotics usage, spine surgeons have adopted several innovative methods to reduce postoperative pain and narcotics consumption. Local infiltrative anesthetics are commonly administered intraoperatively to provide a local field block for several days after surgery. However, these blocks are limited to the areas in which the anesthetic is injected and is technique-dependent. METHODS: A retrospective review of a single surgeon, single institution series of adult patients was conducted between July 2019 and November 2020. Patients were divided into the TLIP or Traditional group depending on which infiltration technique was used. All patients underwent thoracolumbar fusion. Baseline and demographic characteristics and daily narcotics consumption were collected for each patient. All opioid amounts were converted into morphine milligram equivalents (MMEs) for standardization. Analyses were conducted using chi-square exact test and Wilcoxon rank-sum test for categorical and continuous data, respectively. RESULTS: A total of 136 patients were included. Sixty-four (47%) and 72 (53%) managed by TLIP and traditional approaches respectively. Overall mean age was 66.1 years (range, 26-85) with 63 (46%) males and 73 (54%) females, with no significant difference between groups. TLIP patients on average required less hydromorphone than Traditional patients on POD1 (25.1 vs 58.1 mg, P = 0.03) and overall (99.2 vs 184 mg, P = 0.04), less diazepam overall (4.1 vs 10.4 mg, P = 0.01) and less overall opioid medication on POD1 (65.9 vs 95.6 MME, P = 0.04) and overall (221 vs 325 MME, P = 0.03). There was no statistical difference in Percocet use, or any opioid. medications on POD0. TLIP patients experienced shorter length of stay compared to the Traditional group although this difference did not achieve significance (3.0 vs 3.6, P = 0.28). Complication rates were comparable between groups. CONCLUSION: TLIP patients required less hydromorphone and diazepam, as well as total narcotics during their hospital stay, indicating that on average they experienced less severe pain and muscle spasms postoperatively.